Low Power Laser Cutting Of Cotton Fibre Laminate For Electrical Insulation At Low Voltages - Barry Lawrence, Mengga (Universiti Malaysia Sarawak (UNIMAS), 2018)
In this research, low power laser cutting of Cotton Fibre Laminate for electrical insulation at low voltages was investigated. A 1.6 W diode of FABOOL Laser Mini was used to cut the samples with 0.4 mm and 0.8 mm thicknesses. The input parameters in this study were laser power, cutting speed, stand-off distance and number of beam passes. Meanwhile, the output parameters in this study were kerf width, heat affected zone and dimensional accuracy. Microstructure characterisation was conducted using scanning electron microscope in order to observe the cut quality of samples. Digital microscope was used to observe and measure the output parameters. Taguchi Experimental Design was used as an optimisation method in this study. Analysis of Variance (ANOVA) was conducted to analyse the experimental results using Minitab 18 in order to determine the optimum levels of all input parameters. It was found out that the optimum levels of input parameter are different for various types of output parameters. It was also found out that most experiments are largely affected by the cutting speed and least affected by the stand-off distance. Validation of experiments was conducted to verify the optimum levels of all input parameters